The nature of the discretionary power of the criminal judge, its scope, principles, controls, specificities, applications, and stages - Loay Hussein Al-Sherif (International Journal of Law Research and Studies, 2025)
The research aims to clarify the discretionary power of the criminal judge, its scope and principles, and to clarify the controls of the discretionary power of the criminal judge, its specificity and applications. The research also aims to clarify the stages of the discretionary power of the criminal judge, and to clarify the discretionary power of the criminal judge in procedural systems. To achieve the research objectives, the descriptive approach and the comparative inductive approach were used, where the authority of the criminal judge was described in detail, as well as some judicial rulings and various legislations were extrapolated to arrive at general rules governing this authority, and legislation and judiciary in some countries were compared, and successful experiences were benefited from. The research came out with a number of results; the most important of which is that the discretionary power of the criminal judge is not absolute but is restricted by law. The results concluded that the importance of this power lies in achieving individual justice and adapting the punishment to the circumstances of the crime and the personality of the accused. The most important areas in which the judge exercises his discretionary power are: assessing evidence, determining the punishment, and applying precautionary measures. The most important controls that restrict the discretionary power of the judge are: the principle of legality, judicial reasoning, and judicial oversight. The most important recommendations of the research are: amending some legal texts to clarify the scope of the judge’s discretionary power, setting more precise standards for applying precautionary measures, and also reviewing the penalties prescribed for some crimes to ensure that they are commensurate with the seriousness of the crime. The research recommended providing specialized training programs for judges on how to exercise discretionary power properly, holding workshops and seminars to discuss issues related to discretionary power, developing mechanisms for judicial oversight of judges’ decisions and rulings, and publishing judicial rulings to enhance transparency and unify judicial interpretations.